Fuzzy Sumudu Transforms of the Fuzzy Riemann-Liouville Fractional Derivatives About Order - Hameed Hassan, Roaa; Mohammad Abbas, Yasir; ., . (International Journal of Engineering and Technology, 2018)
This work involved fuzyy Sumudu transform (FST) for solving fuzzy fractional differential equations (FFDEs) involving Riemann-Liouvillefuzzy fractional derivative and we find with proof the formulas of fuzzy sumudu transforms for Riemann-Liouville fuzzy fractional derivative about order . Addition, we use the resulting fuzzy Sumudu transform to solve (FFDEs) of order .Â Â